Frontispiece: Mechanobiology in cardiology: Micro‐ and nanotechnologies to probe mechanosignaling (View 2/2021). Issue 2 (8th April 2021) - Yadav, Sharda; Ta, Hang T.; Nguyen, Nam‐Trung
Abstract : Physical forces play a major role in the development of cardiovascular disease. In the recent years, different techniques had been utilized to analyze the changes in biophysical and biomechanical properties of cells in relation to cardiac physiology and pathology. In article number 20200080, Nam‐Trung Nguyen and team present the recent advances in technology for probing mechanobiology signals from the cardiac tissue and elucidate the unmet challenges to completely understand the mechanobiology of cardiac tissues.